1987
DOI: 10.1007/bf01296666
|View full text |Cite
|
Sign up to set email alerts
|

Free radicals and lipid peroxidation in ethanol- or aspirin-induced gastric mucosal injury

Abstract: In this study the role of free radicals and lipid peroxidation as mediators of chemically induced mucosal damage was investigated. Two enzymatic antioxidants, superoxide dismutase or catalase injected intravenously, reduced mucosal damage either by ethanol or aspirin. Of six nonenzymatic antioxidants, given in a wide dose range subcutaneously 30 min before intragastric administration of absolute ethanol, only propyl gallate decreased mucosal damage, while four of the antioxidants tested against aspirin were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
145
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(154 citation statements)
references
References 25 publications
7
145
0
2
Order By: Relevance
“…significantly reduced gastric mucosal hemorrhagic lesions induced by intragas tric H202. It has also been reported that rebamipide can prevent gastric mucosa developing from acute gastric mu cosal lesions induced by ethanol and aspirin (9,10), which are thought to generate reactive oxygen metabolites (3,4). Recently, Yoshikawa et al (12) indicated that rebamipide has a potent activity to scavenge the hydroxyl radical, which is thought to be one of the most toxic free radicals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…significantly reduced gastric mucosal hemorrhagic lesions induced by intragas tric H202. It has also been reported that rebamipide can prevent gastric mucosa developing from acute gastric mu cosal lesions induced by ethanol and aspirin (9,10), which are thought to generate reactive oxygen metabolites (3,4). Recently, Yoshikawa et al (12) indicated that rebamipide has a potent activity to scavenge the hydroxyl radical, which is thought to be one of the most toxic free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1. Effects of intragastric administration of 6% H202 and pretreatment with rebamipide on total glutathione level (GSH) and glutathione peroxidase (GSHpx) and superoxide dismutase (SOD) activities in the gastric mucosa DISCUSSION It has been reported that several necrotizing agents, i.e., ethanol and aspirin, induce gastric mucosal hemor rhagic lesions by promoting the generation of reactive oxy gen metabolites (3,4). Furthermore, it has been indicated that compounds and enzymes that are capable of scaveng ing or inhibiting the generation of reactive oxygen species are able to protect the gastric mucosa from such hemor rhagic lesions (18,19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They elicited a dose dependent and significant (p<0.05) protection against ethanol induced ulcer, but there was little or no protection against indomethacin induced ulcer. Ethanol, a common ulcerogen, produces severe haemorrhagic erosions in the glandular (mucosal) part of the stomach (Ezike et al, 2009) from mechanisms such as direct toxic action, reduction of the secretion of bicarbonate, depletion of gastric wall mucus (Al-Harbi et al, 1997), stimulation of the synthesis and release of leukotriene C 4 (Peskar et al, 1986) and significant production of oxygen free radicals which increase lipid peroxidation and damage cells (Pihan et al, 1987). It also reduces endogenous glutathione and prostaglandin levels and increases the release of histamine, influx of calcium ions and generation of free radicals (Galvin and Szabo, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, oxygenderived free radicals have been postulated to play an important role in the pathogenesis of acute gastric mucosal injuries such as those induced by stress (Govindarajan et al, 2006), ethanol (Salim, 1990 and NSAIDs (Pihan et al, 1987). Scavenging these radicals stimulates the healing process.…”
Section: Dietary Polyphenols Has Protective Effects Against Various Dmentioning
confidence: 99%